Impact of time-of-day on brain morphometric measures derived from T1-weighted magnetic resonance imaging - Trefler, Aaron; Sadeghi, Neda; Thomas, Adam G.; Pierpaoli, Carlo; Baker, Chris I.; Thomas, Cibu (NeuroImage (Orlando, Fla.), 2016)
Measures of brain morphometry derived from T1-weighted (T1W) magnetic resonance imaging (MRI) are widely used to elucidate the relation between brain structure and function. However, the computation of T1W morphometric measures can be confounded by subject-related factors such as head motion and level of hydration. A recent study reported subtle yet significant changes in brain volume from morning to evening in a large group of patient populations as well as in healthy elderly individuals. In addition, there is a growing recognition that factors such as circadian rhythm can impact MRI measures of brain function and structure. Here, we provide a comprehensive assessment of the impact of time-of-day (TOD) on widely used measures of brain morphometry in a group of 19 healthy young adults. Our results show that (a) even in a small group of healthy adult volunteers, a highly significant reduction in apparent brain volume, from morning to evening, could be detected; (b) the apparent volume of all three major tissue compartments – gray matter, white matter, and cerebrospinal fluid – were influenced by TOD, and the magnitude of the TOD effect varied across the tissue compartments; (c) measures of cortical thickness, cortical surface area, and gray matter density computed with widely used neuroimaging software suites (i.e., FreeSurfer, FSL-VBM) were all affected by TOD, while other measures, such as curvature indices and sulcal depth, were not; and (d) the effect of TOD appeared to have a greater impact on morphometric measures of the frontal and temporal lobe than on other major lobes of the brain. Our results suggest that the TOD effect is a physiological phenomenon and that controlling for the effect of TOD is crucial for proper interpretation of apparent structural differences measured with T1W morphometry. •Time of day (TOD) impacts automatically derived measures of brain morphometry derived from T1W images.•The apparent volume of all major tissue compartments are influenced by TOD.•Measures of cortical thickness, cortical surface area and gray matter density are affected by TOD.•TOD has a greater impact on morphometric measures of the frontal and temporal lobe.